Nepotistic Hiring and Poverty From Cultural, Social Class, and Situational Perspectives - Jain, Luke; Gál, Éva; Orosz, Gábor (Frontiers in Psychology, 2022)
Being poor can influence how one makes ethical decisions in various fields. Nepotism is one such area, emerging as kinship-based favoritism in the job market. People can be poor on at least three levels: one can live in a poor country (cross-cultural poverty), be poor compared to others around them (socio-economic poverty), or feel poor in their given situation (situational poverty). We assumed that these levels can simultaneously influence nepotistic hiring decisions among Hungarian (N = 191) and US participants (N = 176). Prior cross-cultural, non-experimental studies demonstrated that nepotism is more prevalent in poorer countries such as Hungary than in richer countries such as the United States. However, contrary to our expectations, in our non-representative, preliminary study, US participants showed stronger nepotistic behavioral tendencies than Hungarians (cross-cultural level). Furthermore, people with lower socioeconomic status had less nepotistic intentions than richer people (socio-economic level). When participants were asked to imagine themselves as a poor person (situational level), they tended to be more nepotistic than had they imagined themselves to be rich. Finally, nepotistic hiring intentions were in general stronger than non-nepotistic hiring intentions. These seemingly paradoxical results were interpreted in the light of the COVID-19 job market context and were explained by the mechanisms described by research on wealth and immoral behaviors, as well as the presence of risk aversion.